New oleanane saponins from the roots of Dendrobangia boliviana identified by LC‐SPE‐NMR - Zebiri, Ilhem (2017)
A LC-SPE-NMR system efficiently contributed to the isolation and identification of five new oleanane saponins from the roots of Dendrobangia boliviana Rusby along with twelve known saponins previously isolated from this plant and of 3- O-βD - glucuronopyranosylphytolaccagenic acid, a compound identified from Diploclisia glaucescens. Their structures were established on the basis of spectral data, mainly HR-ESIMS, 1H-NMR, HSQC, and ROESY, and by comparison with literature data. All but one of these oleanane saponins are glycosides of serjanic or phytolaccinic acid. The remaining one contained a new sapogenin, the 3β,24-dihydroxy-olean-12-en-28,30-dioic acid, 30-methyl ester or 24-hydroxy-serjanic acid, tentatively named dendrobangionic acid.